Acute Kidney Injury: Clinical Characteristics and Short-Term Outcomes in 1,519 Patients - Christina Montgomerie; Jonas Spaak; Marie Evans; Stefan H. Jacobson (Karger Publishers, 2022)
Introduction: Complex integrated information on disease mechanisms and in-hospital outcomes in mild to moderate acute kidney injury (AKI) is scarce. Methods: The Stockholm Prospective AKI Cohort Study (SAKIS) included all patients (≥18 years, n = 1,519) with community-acquired AKI (KDIGO criteria) admitted to the nephrology ward at Danderyd University Hospital, Stockholm, Sweden, between 2009 and 2018. Detailed laboratory measures were registered. Odds ratio for hypo- and hyperkalemia, recovery of kidney function by 30% and 50%, and in-hospital mortality were assessed by logistic regression analysis. Results: Factors independently associated with the presence of hyperkalemia at admission were high age, high serum creatinine (sCr), and low C-reactive protein (CRP). Signs of malnutrition, inflammation, and acidosis were seen in 31% of patients. Kidney recovery, defined as a reduction of sCr by 30% in-hospital (63% of all patients), was associated with higher age, female sex, lower body mass index (BMI), higher hemoglobin, and higher CRP. Factors independently associated with mortality (4.4% of patients) were high age, high BMI, and low albumin. Conclusion: This study provides a detailed description of community-acquired AKI and comprehensive analyses of integrated clinical and laboratory data associated with kidney recovery. Features related to anemia, albuminuria, malnutrition, inflammation, and acidosis associate with partial or moderate short-term recovery of kidney function, with disturbances in potassium homeostasis, and with in-hospital mortality. Future studies are warranted to analyze the long-term consequences of AKI in terms of risk of kidney failure, cardiovascular morbidity, and mortality.